(untitled) (Journal of Nuclear Technology in Applied Science, 2021)
Membrane processes for wastewater treatment have become one of the emerging technologies, which affords a fast development through the past few decades. This study investigated the occurrence of fouling membrane and its composition factors and its effect on membrane performance. In this study, a project pilot scale forward the opposition to cluster transport from one side to the other side of membrane is eventual of the membrane and due to the coat of material on the membrane surface and into the membrane. Effect of severalparameters including trans-membrane compressing (pressure), crossflow velocity, and organic matteron microfiltration (MF) membrane fouling are investigated. The results show that theorganic material existing in the actual wastewater NC30 does not induce foulingin 0.14µm MF membrane with NC fines.